Rediseño arquitectónico del parque “La Cantera” en la ciudad de Ambato, Ecuador - Zumbana Sevilla, Christian Giuseppe (2025)
Public spaces within cities are the scene of the development of human activity, in addition, they act as a regulatory element between the environment and the built environment. In many cases, the various urban phenomena immersed in the development of cities have caused certain public spaces to be affected, which has caused these places to be sites of conflict and insecurity, and consequently generating effects on their immediate context, making it difficult the correct development of human activity and damaging the quality of life of the place. This is the case of La Cantera Park, a public space that, due to various urbanarchitectural factors in the sector to which it belongs, has turned it into an inhospitable and unsafe space. The redesign of La Cantera park aims to reinsert this facility into the urban dynamics of the sector, turning it into a great tourist and recreational attraction, and contributing to improving the quality of life in its immediate context. Through bibliographic search and analysis pertaining to the various urbanarchitectural aspects present in the design of public spaces, the analysis of the current state of La Cantera Park carried out through observation diaries and interviews with residents surrounding the project site. , and the development of intervention strategies generated from the contrast of the theoretical material and contextualization of the project, give rise to the approach of the architectural redesign of this public space.